Finite Element Analysis of a Controlled Dynamization Device for External Circular Fixation - Fernando Ferraz Faria; Carlos Eduardo Miers Gruhl; Rafaela Rebonato Ferro; Rodrigo Nunes Rached; Jamil Faissal Soni; Paula Trevilatto (Revista Brasileira de Ortopedia)
Abstract Objective To virtually prototype a device for external circular fixation of long bone fractures with controlled dynamization made of two different materials and predict their mechanical behavior by using the finite element analysis (FEA) method. Method A software was used for 3D modeling two metal parts closely attached by a sliding dovetail joint and a high-density silicone damper. Distinctive FEAs were simulated by considering two different materials (stainless steel or titanium), modes (locked or dynamized) and loading conditions (static/point or dynamic/0.5 sec) with uniform 150 kg axial load on top of the device. Results The finite elements (FEs) model presented 81,872 nodes and 45,922 elements. Considering stainless steel, the maximum stress peak (140.98 MPa) was reached with the device locked under static loading, while the greatest displacement (2.415 × 10−3 mm) was observed with the device locked and under dynamic loading. Regarding titanium, the device presented the maximum stress peak (141.45 MPa) under static loading and with the device locked, while the greatest displacement (3.975 × 10−3 mm) was found with the device locked and under dynamic loading. Conclusion The prototyped device played the role of stress support with acceptable deformation in both locked and dynamized modes and may be fabricated with both stainless steel and titanium.